Imiona chrzestne w księdze chrztów unickiej parafii Hodyszewo z lat 1759–1801: The baptismal names extract from the register of baptisms in the uniate parish of Hodyszewo from 1759–1801 - Złotkowski, Piotr (Rozprawy Komisji Językowej, 2019)
https://doi.org/10.26485/RKJ/2018/65/17 The article analyzes from a linguistic point of view the baptismal names excerpted from the register of baptisms in the Uniate Parish of Hodyszewo from 1759–1801. For this purpose, the collected onomastic data were divided into four groups, containing names that were used to nominate: Uniate peasants, Catholic peasants, nobility and the remaining population (townsmen, clergy and people without a specific social affiliation). The aim of the analysis was to determine the popularity of particular names and to identify variations of names overall and in each of these ethnic and religious groups. The purpose of research was also to determine the occurrence of polyonymy in the studied source material.